The Lucidarium of Marchetto of Padua - Padova, Marchetto da; Herlinger, Jan W. (Chicago and London The University of Chicago Press, 1985)
''Herlinger deserves the thanks of the scholarly community for having prepared both edition and translation with the most meticulous of critical methods and the greatest of care.''--Leeman L. Perkins, Renaissance Quarterly''An almost archetypal example of unpretentious and honest scholarship.''--Alejandro Enrique Planchart, Journal of the American Musicological Society
Keywords: Music theory